Oldest Preschool Age Child’s Achievement Assessment in Obtaining Basic Education - Ābele, Agita; Tauriņa, Agrita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
New government regulations effective with 01.09.2011 require that preschool teachers produce written reports to children's parents or guardians assessing their children upon graduation. So far preschool teachers had had little experience with similar written forms of assessment, and this creates questions regarding the assessment design and implementation. This work's aim was to theoretically evaluate the problems of preschool children's achievement assessment and analyze results of pedagogues' inquiry on potential ways of solving them. This article explores some of the more pressing questions, as well as the consequences of poor assessment design such as conflict with parents, mislabeling of children, affecting children's motivations, effect on teacher's and institution's reputation, additional workload, and resource consumption. Authors look at experience accumulated in other countries while tackling these issues and suggest using a dual evaluation model.